Thermal Performance Study of Parallel and Radial Divergence Microchannel Arrangement Using Numerical Method - Ahmed, Sahib Shihab; Rageb, Abdul Muhsin A. (Basrah Journal for Engineering Sciences, 2020)
This study presents three-dimensional numerical simulations of single-phase laminar flow and forced convection heat transfer of water in a five-layer microchannel heat sink with two channel configurations: radial arrangement and parallel divergence channels. The thermal performance and pressure drop characteristics were evaluated under identical operating conditions, including a constant mass flow rate of 3.925 × 10⁻⁴ kg/s and a uniform heat flux of 90 W/cm². The results indicated that the radial microchannel configuration significantly enhanced both hydrodynamic and thermal performance compared with the parallel divergence design. Specifically, the pressure drop was reduced by approximately 32.5%, the overall performance index increased by about 1.5, and improved temperature uniformity across the heat sink was achieved. These findings demonstrate the superiority of the radial microchannel arrangement for high-heat-flux thermal management applications.